APLICATION OF CATALYTIC DIELECTRIC BARRIER DISCHARGE PLASMA REACTOR FOR CO-GENERATION OF SYNTHESIS GAS AND HIGHER HYDROCARBONS - istadi istadi; Amin N.A.S. Amin (Reaktor, 2006)
This paper deals with potential application of hybrid catalytic DBD plasma reaktor for the co-generation of  C2 hydrocarbons and synthesis gases from methane and carbon dioxide. The synergism of the catalyst, feed ratio and the plasma discharge affect the products, distribution, particularly C2 hydrocarbons selectivity . The CH,CO2 feed ratio total feed flow rate, and the discharge voltage incatalytic BDB plasma reactor systems shoe significant effects on the reactor performances. However increasing the reactor wall temperature has no apparent influence on the selectivity to C2 hydrocarbons and hydrogen within the investigated range. The hybrid catalytic DBD plasma rectorwas more suitable for CO2OCM process than the conventional catalytic reactor over CaO-MnO/CeO2catalyst